Shared virtual learning environments in higher education - Margarita R. Rodríguez Gallego; Antonia López Martínez (Universitat Politècnica de València, 2013)
There is an increasing demand for virtual platforms based on the concept of Web 2.0 and on Personal Learning Networks (PLN) as these guarantee conversations between educational agents and cooperation aimed at the joint knowledge production. From this point of view, Virtual Learning Environments (VLE) have emerged in which new applications adapted to users' needs are configured, integrated and combined. The ultimate purpose of this experience is the creation of a shared virtual environment to ensure that learning is not linked exclusively to rote activity. Through the combined use of the virtual platform, Web 2.0 tools and social networking, students can create their own workspace in which the search and processing of information, as well as the creation of learning resources and collaboration tasks are reflected. Our shared virtual learning environment has been tested, implemented and evaluated in the second semester, as part of the General Teaching Methodology course in the Faculty of Education at the University of Seville (Spain) during the 2009 -2010 academic year. A survey reveals interesting facts about the success of the shared virtual environment in relation to the motivation and learning outcomes of students.